2019
DOI: 10.3390/molecules24234260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasonic-Assisted Extraction on the Physicochemical Properties of Different Walnut Proteins

Abstract: The effects of ultrasonic-assisted extraction (UAE, 200 W, 20 min) on the yield and physicochemical properties of different walnut proteins (WNPs, including albumin, globulin, and glutelin) were investigated. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis indicated that UAE could result in protein molecular fragmentation of albumin, but did not affect the major bands of globulin and glutelin. The CD spectra demonstrated that different WNPs obtained by UAE had different changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…A value of 0.6 ± 0.0 mg/g was attained for the MeOH-H 2 O extract, whereas they were absent in the EtOAc fraction. The low levels of protein content can be caused by the ultrasonic extraction, which leads to protein denaturation, as proven by some researchers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…A value of 0.6 ± 0.0 mg/g was attained for the MeOH-H 2 O extract, whereas they were absent in the EtOAc fraction. The low levels of protein content can be caused by the ultrasonic extraction, which leads to protein denaturation, as proven by some researchers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…oleifera leaves than conventional solvent extraction. The shear force and cavitation effect produced by ultrasonic can destroy the plant cell membrane, increase the contact surface with the solvent, and cause protein fragmentation (Lv et al., 2019). Also, microwaves generate heat inside the material, which contribute to a quick heating in less time compared to the traditional heating methods, thereby disrupting the cells and facilitate release the protein inside the cell wall into the solvent (Djilani et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when microwave power exceeded a certain value, the high microwave energy would disturb the interactions of molecular (Xu et al., 2018) and led to partial protein denaturation. Likewise, higher temperature or longer irradiation time for ultrasound and microwave extraction will destabilize the aqueous envelope of the proteins, destroy the hydrogen bond and structure of the protein, which could accelerate protein denaturation and precipitation, thus made the leaf protein solubility worse (Lv et al., 2019). Also, large amount of solvent can result in insufficient energy diffusion in the reaction field, thereby hindering cell rupture and protein dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…The natural walnut protein has a compact stereostructure, and most of its cleavage sites are contained in the protein, which makes it difficult to be hydrolyzed by protease. In order to solve this problem, Lv et al [27] and Li et al [28] studied the effect of ultrasonic assistance on the enzymatic hydrolysis of walnut residue. The results showed that ultrasonic-assisted hydrolysis of walnut protein had a positive effect on the reaction characteristics and energy efficiency.…”
Section: Enzymatic Preparationmentioning
confidence: 99%